EDUKASI SERTA PRAKTIK PEMBUATAN TONER WAJAH HERBAL DARI TIMUN DAN ALOEVERA SEBAGAI UPAYA PERAWATAN KULIT REMAJA YANG RAMAH LINGKUNGAN DAN BEBAS BAHAN SINTETIS - sulasmi, sulasmi (Jurnal Pengabdian Masyarakat Putri Hijau, 2025)
The increasing use of chemical ingredients in cosmetic products poses a risk of long-term adverse effects on skin health, prompting a return to the utilization of natural ingredients. This community service activity aims to provide education and hands-on practice in making herbal face toner for students of SMAS Al Washliyah 3 Medan. The main ingredients used are cucumber (Cucumis Sativus L) and aloe vera (Aloe Vera L), which are known for their moisturizing, soothing, and cooling properties for the skin. The activity methods include material presentation, a question-and-answer session, and toner-making practice to enhance participants' understanding and skills. Through this program, it is expected that adolescents will gain awareness of the importance of safe and synthetic-free skin care, be able to create natural care products independently, and become wiser in choosing environmentally friendly cosmetic products.